The PI3K inhibitor pictilisib and the multikinase inhibitors pazopanib and sorafenib have an impact on Rac1 level and migration of medulloblastoma in vitro. Issue 23 (15th November 2022) - Schoen, Leonie F.; Craveiro, Rogerio B.; Pietsch, Torsten; Moritz, Thomas; Troeger, Anja; Jordans, Silvia; Dilloo, Dagmar
Abstract: Metastatic disease is the leading cause of death in children suffering from medulloblastoma and a major treatment challenge. The evidence of leptomeningeal dissemination defines the most aggressive tumours and is associated with increased mortality; thus, inhibition of migration as a factor involved in the process of metastatic disease is fundamental for the treatment and prevention of metastatic dissemination. Targeting the small Rho GTPases Rac1 has been shown to effectively impair medulloblastoma cell migration in vitro. Yet clinically applicable selective Rac1 inhibitors are still lacking. In view of the pertinent oncogenic role of the PI3K signalling cascade and tyrosine kinase‐mediated signalling pathways in medulloblastoma, we explored clinically available targeted therapeutics to this effect. Here, we show that Rac1 is expressed in both the cytoplasm and nucleus in the medulloblastoma cell lines Daoy and MEB‐Med‐8A representative of two high risk medulloblastoma entities. We demonstrate that activated Rac1 is subject to substantial downmodulation following administration of the clinically available inhibitor of the PI3K pathway Pictilisib (GDC‐0941) and the multityrosine kinase inhibitors Pazopanib and Sorafenib. The application of those drugs was associated with reduced mobility of the medulloblastoma cells and alterations of the actin skeleton. Of note, PI3K inhibition reveals the strongest anti‐migratory effect in Daoy cells. Thus, our in vitro observations provide new insights into different strategies of blocking Rac1 and inhibiting migration in medulloblastoma employing clinically available agents paving the way for confirmatory studies in in vivo models.